Acute fulminating viral myocarditis: clinically mimicking ARDS - Sit, N K; Saha, K; Bandyopadhyay, A; Sarkar, S (Bangladesh Journal of Medical Science, 2012)
Viral myocarditis usually presented with influenza like manifestations, cardiac symptoms and signs related to myocarditis. We are presenting a case which was clinically mimicking acute respiratory distress syndrome but careful history taking with chest x-ray examination saves life of the patient DOI: http://dx.doi.org/10.3329/bjms.v11i3.11735 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12